Subordinate officers in Xenophon's Anabasis - Rood, T; Huitink, L (Histos, 2016)
This chapter focuses on Xenophon’s treatment of divisions within the command structure presented in the Anabasis, and in particular on three military positions that are briefly mentioned—the taxiarch, ὑποστράτηγος, and ὑπολόχαγος. Arguing against the prescriptive military hierarchies proposed in earlier scholarship, it suggests that ‘taxiarch’ should be understood fluidly and that the appearance of both the ὑποστράτηγος and the ὑπολόχαγος may be due to interpolation. The chapter also includes discussion of two types of comparative material: procedures for replacing dead, absent, or deposed generals at Athens and Sparta in the Classical period, and the lexical development of subordinate positions with the prefix ὑπο-.